Influenza Viruses: Innate Immunity and mRNA Vaccines - Lee, SangJoon; Ryu, Jin-Hyeob (Frontiers in Immunology, 2021)
The innate immune system represents the first line of defense against influenza viruses, which cause severe inflammation of the respiratory tract and are responsible for more than 650,000 deaths annually worldwide. mRNA vaccines are promising alternatives to traditional vaccine approaches due to their safe dosing, low-cost manufacturing, rapid development capability, and high efficacy. In this review, we provide our current understanding of the innate immune response that uses pattern recognition receptors to detect and respond to mRNA vaccination. We also provide an overview of mRNA vaccines, and discuss the future directions and challenges in advancing this promising therapeutic approach.